Comparison between clinical and audiological results of tympanoplasty with modified sandwich technique and underlay technique - Nemade,Sanjana Vijay (2018)
Abstract Introduction: Surgical repair of the tympanic membrane, termed a type one tympanoplasty is a tried and tested treatment modality. Overlay or underlay technique of tympanoplasty is common. Sandwich tympanoplasty is the combined overlay and underlay grafting of tympanic membrane. Objective: To describe and evaluate the modified sandwich graft (mediolateral graft) tympanoplasty using temporalis fascia and areolar fascia. To compare the clinical and audiological outcome of modified sandwich tympanoplasty with underlay tympanoplasty. Methods: A total of 88 patients of chronic otitis media were studied. 48 patients (Group A) underwent type one tympanoplasty with modified sandwich graft. Temporalis fascia was underlaid and the areolar fascia was overlaid. 48 patients (Group B) underwent type one tympanoplasty with underlay technique. We assessed the healing and hearing results. Results: Successful graft take up was accomplished in 47 patients (97.9%) in Group A and in 40 patients (83.3%) Group B. The average Air-Bone gap closure achieved in Group A was 24.4 ± 1.7 dB while in Group B; it was 22.5 ± 3.5 dB. Statistically significant difference was found in graft healing rate. Difference in hearing improvement was not statistically significant. Conclusion: Double layered graft with drum-malleus as a ‘meat' of sandwich maintains a perfect balance between sufficient stability and adequate acoustic sensitivity.